2016
DOI: 10.1039/c6en00031b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bactericidal toxicity of silver nanoparticles by the antibiotic gentamicin

Abstract: The alteration of properties of nanomaterials in the environment may change the interaction of the nano–bio interface and the corresponding bio-responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…The results obtained from this study are consistent with that of other researches. Indeed, gentamycin plus Ag-NPs in several studies demonstrated enhanced or even synergistic antibacterial effect against (Barapatre, et al 2016;Chhibber, et al 2017;Ebrahimi, et al 2017;Jamaran and Zarif 2016;Katva, et al 2017;Mohamed, et al 2017;Panacek, et al 2015;Satapathy, et al 2017;Verma, et al 2017;Wang, et al 2016).Moreover, in a good agreement with reported data in the literature, penicillin (Ebrahimi, et al 2017;Panacek, et al 2015) in contrary to some studies (Deng, et al 2016;Natan and Banin 2017;Wang, et al 2016) and ciprofloxacin in the case of human strains (Mohamed, et al 2017;Yallappa, et al 2015) in accord with our data (Panacek, et al 2015) showed significant increase in antibacterial activities when conjugated with Ag-NPs. Furthermore, tetracycline (Deng, et al 2016;Ebrahimi, et al 2017;Natan and Banin 2017), amoxicillin (Mohamed, et al 2017), cephalosporin (Refat, et al 2017), erythromycin (Yallappa, et al 2015 showed partially increase in antibacterial activities in the presence of Ag-NPs.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained from this study are consistent with that of other researches. Indeed, gentamycin plus Ag-NPs in several studies demonstrated enhanced or even synergistic antibacterial effect against (Barapatre, et al 2016;Chhibber, et al 2017;Ebrahimi, et al 2017;Jamaran and Zarif 2016;Katva, et al 2017;Mohamed, et al 2017;Panacek, et al 2015;Satapathy, et al 2017;Verma, et al 2017;Wang, et al 2016).Moreover, in a good agreement with reported data in the literature, penicillin (Ebrahimi, et al 2017;Panacek, et al 2015) in contrary to some studies (Deng, et al 2016;Natan and Banin 2017;Wang, et al 2016) and ciprofloxacin in the case of human strains (Mohamed, et al 2017;Yallappa, et al 2015) in accord with our data (Panacek, et al 2015) showed significant increase in antibacterial activities when conjugated with Ag-NPs. Furthermore, tetracycline (Deng, et al 2016;Ebrahimi, et al 2017;Natan and Banin 2017), amoxicillin (Mohamed, et al 2017), cephalosporin (Refat, et al 2017), erythromycin (Yallappa, et al 2015 showed partially increase in antibacterial activities in the presence of Ag-NPs.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, gentamicin molecules contain many active groups such as amino and hydroxyl, which react easily with Ag nanoparticles by chelation. 29,50 The complex (Ag-gentamicin) may further bind to DNA, preventing DNA unwinding. Also, the Ag-gentamicin could potentially keep a more stable structure, thus potentially leading to a longterm antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…95, 268275 Current ENM-based antibacterial applications usually rely on mechanisms acting through toxic ions, ROS, oxidative stress and membrane damage elicited by NPs (e.g. Ag, CuO and ZnO NPs, carbon nanotubes and graphene derivatives) bound to bacterial cell wall or taken up by bacterial cells.…”
Section: Discussionmentioning
confidence: 99%